2011
DOI: 10.1111/j.1755-3768.2011.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in vaulting of myopic and toric implantable collamer lenses in different lighting conditions

Abstract: . Purpose:  To evaluate the changes in vaulting of myopic and toric Implantable Collamer Lenses (ICLs) in different lighting conditions. Methods:  Thirty‐seven eyes of 37 patients implanted with a myopic ICL and 26 eyes of 26 patients implanted with a toric ICL were examined using Visante optical coherence tomography (OCT) in photopic (257 lux) and mesopic (2 lux) conditions. Pupil diameter and distance changes between the ICL and adjacent intraocular structures were measured. Results:  The mean horizontal pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
4
19
1
Order By: Relevance
“…11 A significant mean reduction in vaulting (À40 mM) in eyes implanted with V4 ICLs also has been reported under photopic conditions of 257 lux. 13 Consistent with these 2 studies, in the eyes implanted with V4 ICLs in our study, a comparable reduction in vaulting (À88.6 mM) was observed, showing the highest amount of vaulting changes between photopic and mesopic conditions. A possible explanation is that the light intensity provided by a light source such as a penlight or room light may affect changes in vaulting, based on previous studies that showed increased light stimulus intensity was associated with an increase in direct light reflex amplitude and the maximum rate of constriction.…”
Section: In This Study We Measured Postoperative Iclsupporting
confidence: 92%
See 4 more Smart Citations
“…11 A significant mean reduction in vaulting (À40 mM) in eyes implanted with V4 ICLs also has been reported under photopic conditions of 257 lux. 13 Consistent with these 2 studies, in the eyes implanted with V4 ICLs in our study, a comparable reduction in vaulting (À88.6 mM) was observed, showing the highest amount of vaulting changes between photopic and mesopic conditions. A possible explanation is that the light intensity provided by a light source such as a penlight or room light may affect changes in vaulting, based on previous studies that showed increased light stimulus intensity was associated with an increase in direct light reflex amplitude and the maximum rate of constriction.…”
Section: In This Study We Measured Postoperative Iclsupporting
confidence: 92%
“…Additionally, anterior protrusion or posterior movement of the crystalline lens might follow, all of which have been demonstrated previously in eyes implanted with conventional ICLs. 11,13 However, our results in eyes implanted with V4c ICLs did not support light-induced movement of the crystalline lens, which was proven by an unchanging ACD according to differing lighting conditions. Based on these results, it is highly probable that the backward movement of the V4c ICL toward the anterior surface of the crystalline lens, induced by constriction of the pupil under photopic conditions, could be the main contributor to dynamic changes in vaulting.…”
Section: In This Study We Measured Postoperative Iclcontrasting
confidence: 51%
See 3 more Smart Citations